Wear behavior at margins of direct composite with CAD/CAM composite and enamel - Lassila Lippo; Novotny Rudolf; Säilynoja Eija; Vallittu Pekka K.; Garoushi Sufuan (Germany, 2025)
Objectives: The aim was to investigate the two-body wear at the marginal area between direct filling composites and substrate of CAD/CAM composites or enamel.
Materials and methods: Flat specimens were prepared from CAD/CAM composites (CERASMART 270 and SFRC CAD) and bovine enamel. A box-shaped cavity cut into CAD/CAM composites and enamel surfaces was made. The prepared cavity in CAD/CAM composites was treated with a primer, while in enamel, the cavity was treated with an adhesive. Three conventional composites (Universal Injectable, G-aenial A'Chord, and Filtek Bulk Fill) and one short fiber composite (everX Flow) were placed and cured in the prepared cavities. A two-body wear test was conducted with 15,000 chewing cycles using a dual-axis chewing simulator. The specimens (n = 5/per group) were positioned to produce wear (load = 20 N) across the marginal area between filling composites and substrates. The wear depth was analyzed using a 3D optical profilometer. SEM was used to evaluate the wear behavior and margins between the filling and substrate materials.
Results: All composites used displayed different wear behavior (20-39 µm) (p < 0.05). The highest wear values were recorded for A'Chord and Filtek, while the lowest values were for Injectable and CERASMART 270. The data analysis showed that the wear behavior of substrate materials depends on the filling materials used at margins (p < 0.05). The marginal breakdown was seen only between bovine enamel and filling composites.
Conclusions: The use of the two-body wear simulation method revealed important information about the behavior of the filling composites at the marginal area with CAD/CAM composites or bovine enamel substrates.
Clinical relevance: The marginal breakdown related to the material combination at the bonding region.